6+4s-5=5s+6-2s

Simple and best practice solution for 6+4s-5=5s+6-2s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+4s-5=5s+6-2s equation:


Simplifying
6 + 4s + -5 = 5s + 6 + -2s

Reorder the terms:
6 + -5 + 4s = 5s + 6 + -2s

Combine like terms: 6 + -5 = 1
1 + 4s = 5s + 6 + -2s

Reorder the terms:
1 + 4s = 6 + 5s + -2s

Combine like terms: 5s + -2s = 3s
1 + 4s = 6 + 3s

Solving
1 + 4s = 6 + 3s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-3s' to each side of the equation.
1 + 4s + -3s = 6 + 3s + -3s

Combine like terms: 4s + -3s = 1s
1 + 1s = 6 + 3s + -3s

Combine like terms: 3s + -3s = 0
1 + 1s = 6 + 0
1 + 1s = 6

Add '-1' to each side of the equation.
1 + -1 + 1s = 6 + -1

Combine like terms: 1 + -1 = 0
0 + 1s = 6 + -1
1s = 6 + -1

Combine like terms: 6 + -1 = 5
1s = 5

Divide each side by '1'.
s = 5

Simplifying
s = 5

See similar equations:

| 5+2x=4x-9 | | 3x-14=2x-8 | | (3+2x)*2=2+0x | | X^4+13x^3-48x^2=0 | | 0=2*sin(2x) | | 8v+w+7-8w+2w= | | m+3.5=4.2 | | 2(3h-7)=76 | | 3x+(-3x)=5 | | 2+3x+4-1= | | 0.16y+0.08(y+9000)=2400 | | 6(t-3)+4t=5(2t+5)-13 | | .11x-400-.03x=840 | | 4x+6+3x+4=(-40)+4 | | 3z-836=-77 | | Y+8=2y-4 | | -3x+10=94+4x | | 5y^2-7y=-2 | | 27=3(2x-7) | | -11x-400-.03x=840 | | 27=15+9 | | 3x-9=5x+2 | | -1.08=0.9v | | 2x+2y=2x+9 | | 4x^2-8x+4y^2+12y-131=0 | | 6s+2=-10 | | K-7+6= | | 12n-17n+6=32 | | v^2-4vx-12x^2=0 | | 3x(2)=12+5x | | 96=16+2x | | 9(t-6)+3=6(2t+3)-9 |

Equations solver categories